Long‐term follow‐up of chronic central serous chorioretinopathy after successful treatment with photodynamic therapy or micropulse laser. Issue 7 (10th February 2021) - van Rijssen, Thomas J.; van Dijk, Elon H. C.; Scholz, Paula; Breukink, Myrte B.; Dijkman, Greet; Peters, Petrus J. H.; Tsonaka, Roula; Keunen, Jan E. E.; MacLaren, Robert E.; Hoyng, Carel B.; Downes, Susan M.; Fauser, Sascha; et al.
Abstract: Purpose: To describe the treatment outcomes and recurrence risk of chronic central serous chorioretinopathy (cCSC) in patients who had complete resolution of subretinal fluid (SRF) after either primary half‐dose photodynamic therapy (PDT) or high‐density subthreshold micropulse laser (HSML) in the PLACE trial. Methods: This multicentre prospective follow‐up study evaluated cCSC patients at 1 year after completion of the PLACE trial. Outcomes included: complete resolution of SRF on OCT, best‐corrected visual acuity (BCVA) in Early Treatment of Diabetic Retinopathy Study (ETDRS) letters, retinal sensitivity on microperimetry and a visual function questionnaire (NEI‐VFQ25). Results: Twenty‐nine out of 37 patients who received half‐dose PDT and 15 out of 17 patients who received HSML could be evaluated at final visit. At final visit, 93% of the patients treated with half‐dose PDT had complete resolution of SRF, compared with 53% of HSML‐treated patients (p = 0.006). At final visit, the mean estimate increase in the PDT group compared with the HSML group was + 2.1 ETDRS letters, +0.15 dB for the retinal sensitivity and + 5.1 NEI‐VFQ25 points (p = 0.103, p = 0.784 and p = 0.071, respectively). The mean estimated central retinal thickness in the half‐dose PDT group was −7.0 µm compared with the HSML group (p = 0.566). The mean estimated subfoveal choroidal thickness in the half‐dose PDT group was −16.6 µm compared with the HSML group (p = 0.359). Conclusion: At 20 months after treatment, cCSC patients successfully treated with half‐dose PDT are less likely to have recurrences of SRF compared with those successfully treated with HSML. However, functional outcomes did not differ.